Development and immunochemical evaluation of a novel chicken IgY antibody specific for KLK6 - Sotiropoulou Georgia; Pampalakis Georgios; Prosnikli Evangelia; Evangelatos Gregory P; Livaniou Evangelia (Chemistry Central Journal, 2012)
Abstract Background Human kallikrein-related peptidase 6 (KLK6) has been implicated in various types of cancer and in neurodegenerative and demyelinating diseases including multiple sclerosis. Further, anti-KLK6 antibodies attenuated disease manifestations in the mouse model of multiple sclerosis. Availability of specific antibodies against KLK6 is fundamental to the development of improved diagnostic and/or immunotherapeutic applications. Here, we exploited the enhanced immunogenicity of mammalian proteins in avian species to generate a polyclonal antibody against KLK6. Results Chicken were immunized with recombinant KLK6 and antibodies Y (IgYs) were purified from egg yolk with a simple procedure and evaluated for KLK6 detection by ELISA and Western blot using recombinant proteins and human cell lysates and supernatants. The anti-KLK6 Y polyclonal exhibited high affinity for KLK6 with a detection limit of 30 fmol. On the other hand, the widely used rabbit polyclonal antibody that was raised against the same recombinant KLK6 had a detection limit of 300 fmol. Moreover, the IgYs did not display any crossreactivity with recombinant KLKs or endogenous KLKs and other cellular proteins. Conclusions Based on its high specificity and sensitivity the developed anti-KLK6 IgY is expected to aid the development of improved diagnostic tools for the detection of KLK6 in biological and clinical samples.